2012
DOI: 10.1007/s00441-012-1502-9
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 26 facilitates gastrointestinal bacterial infection in vitro

Abstract: Escherichia coli, including enteropathogenic E. coli (EPEC), represents the most common cause of diarrhoea worldwide and is therefore a serious public health burden. Treatment for gastrointestinal pathogens is hindered by the emergence of multiple antibiotic resistance, leading to the requirement for the development of new therapies. A variety of mechanisms act in combination to mediate gastrointestinal-bacterial-associated diarrhoea development. For example, EPEC infection of enterocytes induces attaching and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Recently, it has been demonstrated that Cx43 contribute to the diarrhea caused by Citrobacter rodentium in mice (Guttman et al , 2010). A more recent in vitro study showed that loss of functional Cx26 expression provided protection against GI bacterial pathogens, and Cx26 represents a potential therapeutic target for GI bacterial infection (Simpson et al , 2013). Therefore, accumulating evidences suggest the emerging roles of connexins in GI pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that Cx43 contribute to the diarrhea caused by Citrobacter rodentium in mice (Guttman et al , 2010). A more recent in vitro study showed that loss of functional Cx26 expression provided protection against GI bacterial pathogens, and Cx26 represents a potential therapeutic target for GI bacterial infection (Simpson et al , 2013). Therefore, accumulating evidences suggest the emerging roles of connexins in GI pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…However, carriers of the common recessive deafness-associated GJB2 mutations 35delG and R143W have been reported to exhibit a normal but slightly thicker epidermis Guastalla et al, 2009). In vitro studies, using three-dimensional (3D) skin culture models, support these histological and ultrasound observations, and suggest that loss of functional Cx26 might confer improved barrier function in the skin (and also in the gut), with increased protection from bacterial infection (Man et al, 2007;Simpson et al, 2013).…”
Section: The Importance Of Gap Junctionsmentioning
confidence: 95%
“…Gap junctions are major channels that allow cells to communicate with one another by facilitating intercellular communication, including the transfer of Ca 2+ , a fundamental ion in keratinocyte differentiation, and small molecules of ,1 kDa -such as inositol triphosphate (IP 3 ) -between cells. In the skin, gap junctions appear to regulate a number of cellular processes, including wound healing, differentiation and barrier function (Goliger and Paul, 1995;Coutinho et al, 2003;Qiu et al, 2003;Djalilian et al, 2006;Mori et al, 2006;Man et al, 2007;Kandyba et al, 2008;Simpson et al, 2013), and their role in epidermal integrity is reviewed elsewhere (Martin et al, 2014).…”
Section: The Importance Of Gap Junctionsmentioning
confidence: 99%
“…These data start to provide an explanation why ‘loss of function’ mutations are linked with non‐inflammatory disorders of the skin. In parallel studies, Kelsell and colleagues have observed that non‐functional Cx26 mutations associated with NSHI confer resistance to enteric infections such as Shigella flexneri [21,111]. The effect of S. flexneri is mediated via cellular invasion, shown to activate Cx26 hemichannel signalling [108,112].…”
Section: Connexins the Skin Microflora And Innate Immunitymentioning
confidence: 97%